Optimizing the Synergy Between Hotel and Event Organizer to Enhance Palembang City's Appeal as a Mice and Event Destination - Wisanggeni Agus Priyanto; Ahmad Kurniawan; Iwan Riady; Melati Pratama (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2025)
This study aims to examine the optimization of synergy between hotels and event organizers in enhancing the appeal of Palembang City as a Meeting, Incentive, Convention, and Exhibition (MICE) destination. Using a mixed-methods approach, qualitative data were analyzed thematically using NVivo software, while quantitative data were analyzed using descriptive and inferential statistics. Thematic findings reveal that intensive collaboration among stakeholders is the key to successful synergy, but there are still limitations in terms of international standard facilities and human resource competencies. Digital technology, particularly for hybrid events and marketing management, is also an important requirement. Quantitative analysis shows that the quality of facilities and the effectiveness of communication significantly influence participant satisfaction and the enhancement of destination appeal. The systematically built synergy has a tangible positive impact on MICE development in Palembang. Therefore, synergy must be accompanied by concrete investment in facilities and technology as the foundation for sustainable and competitive MICE destination development. This study contributes to the development of MICE tourism industry strategies in emerging destinations through a collaborative, integrative, and adaptive approach to global trends. Keywords: Synergy, Hotel, Event Organizer, MICE Destination, Palembang, Collaboration, Digital Transformation, Tourism Development.